Odpowiedzi

Najlepsza Odpowiedź!
2010-01-19T18:39:08+01:00
3x-2y=5 /•2
-2x+6y=9 /•3

6x-4y=10
-6x+18y=27
+------------ (dodajemy te wyrażenia)
14y=37/:14
y= 2,64

-2x+6y=9
y= 2,64

-2x=9-6y
y=2,64

-2x=9-6•2,64
-2x=9-15,84
-2x= -6,84/:(-2)
x= 3,42

x=3,42
y=2,64

to jest w przybliżeniach podane... bo za dużo po przecinkach było;P
2010-01-19T18:45:46+01:00
3x-2y=5 / *3
-2x+6y=9

9x-6y=15
-2x+6y=9

7x=24
x=3³₇

-2x+6y=9
y=2⁹₁₄
2010-01-19T18:50:24+01:00
[3x-2y=5 |*3
[-2x+6y=9
[9x-6y=15
[-2x+6y=9

7x=24 |:7

x~3,428